Assessing the human health risks of perfluorooctane sulfonate by in vivo and in vitro studies. (May 2019) - Zeng, Zhuotong; Song, Biao; Xiao, Rong; Zeng, Guangming; Gong, Jilai; Chen, Ming; Xu, Piao; Zhang, Peng; Shen, Maocai; Yi, Huan
Abstract: The wide use of perfluorooctane sulfonate (PFOS) has led to increasing concern about its human health risks over the past decade. In vivo and in vitro studies are important and effective means to ascertain the toxic effects of PFOS on humans and its toxic mechanisms. This article systematically reviews the human health risks of PFOS based on the currently known facts found by in vivo and in vitro studies from 2008 to 2018. Exposure to PFOS has caused hepatotoxicity, neurotoxicity, reproductive toxicity, immunotoxicity, thyroid disruption, cardiovascular toxicity, pulmonary toxicity, and renal toxicity in laboratory animals and many in vitro human systems. These results and related epidemiological studies confirmed the human health risks of PFOS, especially for exposure via food and drinking water. Oxidative stress and physiological process disruption based on fatty acid similarity were widely studied mechanisms of PFOS toxicity. Future research for assessing the human health risks of PFOS is recommended in the chronic toxicity and molecular mechanisms, the application of various omics, and the integration of toxicological and epidemiological data. Graphical abstract: Unlabelled Image Highlights: Assessing human health risks of PFOS by in vivo and in vitro studies are reviewed. Exposure to PFOS can cause significant human health risks. The chronic toxicity and molecular mechanisms need further study. Integration of the toxicological and epidemiological data is recommended.